Identification of bovine CpG SNPs as potential targets for epigenetic regulation via DNA methylation - Maldonado, Mariângela B.C. [UNESP]; De Rezende Neto, Nelson B.; Nagamatsu, Sheila T.; Carazzolle, Marcelo F.; Hoff, Jesse L.; Whitacre, Lynsey K.; Schnabel, Robert D.; Behura, Susanta K.; McKay, Stephanie D.; Taylor, Jeremy F.; Lopes, Flavia L. [UNESP] (Public Library of Science (PLoS), 2019)
Methylation patterns established and maintained at CpG sites may be altered by single nucleotide polymorphisms (SNPs) within these sites and may affect the regulation of nearby genes. Our aims were to: 1) identify and generate a database of SNPs potentially subject to epigenetic control by DNA methylation via their involvement in creating, removing or displacing CpG sites (meSNPs), and; 2) investigate the association of these meSNPs with CpG islands (CGIs), and with methylation profiles of DNA extracted from tissues from cattle with divergent feed efficiencies detected using MIRA-Seq. Using the variant annotation for 56,969,697 SNPs identified in Run5 of the 1000 Bull Genomes Project and the UMD3.1.1 bovine reference genome sequence assembly, we identified and classified 12,836,763 meSNPs according to the nature of variation created at CpGs. The majority of the meSNPs were located in intergenic regions (68%) or introns (26.3%). We found an enrichment (p<0.01) of meSNPs located in CGIs relative to the genome as a whole, and also in differentially methylated sequences in tissues from animals divergent for feed efficiency. Seven meSNPs, located in differentially methylated regions, were fixed for methylation site creating (MSC) or destroying (MSD) alleles in the differentially methylated genomic sequences of animals differing in feed efficiency. These meSNPs may be mechanistically responsible for creating or deleting methylation targets responsible for the differential expression of genes underlying differences in feed efficiency. Our methyl SNP database (dbmeSNP) is useful for identifying potentially functional epigenetic polymorphisms underlying variation in bovine phenotypes.